Cyclists' Injuries in Traffic - Eduard Missoni; Igor Bogović; Vinko Višnjić (Promet (Zagreb), 2004)
Among numerous participants in road traffic there are alsothe cyclists. Cycling has become during the recent years one ofthe major components of the modem living, even in Croatia. Inalmost all the developed countries of the world, cycling isemphasised as an activity which improves health and contributesto the improvement of overall physical fitness and environmentalprotection. During the period between 1 January 1996and 31 December 1999, an analysis of the number of cyclist accidentsin road traffic was carried out. Special attention waspaid to the number of injured cyclists. In 1996, in road traffic,there were 1,218 cyclist accidents in which 912 (74.9%) cyclistswere injured. In 1997, there were 1,146 incidents and accidents,with 854 (74.5%) injured persons. In 1998, there were 1,167accidents, 887 (76.0%) injured. In the last study in 1999, thetotal number of cyclist accidents amounted to 1,230, and thenumber of the injured cyclists was 924 (75.1% ).Every event resulting in a more or less severe disability is agreat distress and great damage to every injured person as individualas well as for the family and eventually for the society asa whole. This paper recommends certain measures and proceduresthat should substantially reduce the traffic accidents andincidents which involve cyclists.